New Medieval Literatures 18 - Ashe, Laura; Knox, Philip; Kawton, David; Scase, Wendy (New Medieval Literatures, 2018)
An invigorating annual for those who are interested in medieval textual cultures and open to ways in which diverse post-modern methodologies may be applied to them." Alcuin Blamires Review of English Studies"